Adapting a Social Skills Intervention for Children with Autism within an Urban Specialty Community Clinic. Issue 4 (3rd December 2018) - Sauvé, Jennifer S.; O'Haire, Chelsea; Hall, Heather; Lane, Christianne; Hudson, Bradley O.
ABSTRACT: Children and adolescents with autism spectrum disorders typically have social skills deficits that put them at risk for experiencing peer victimization and the development of psychiatric illness. Social skills training groups have been developed to provide an evidence-based practice to target these difficulties. However, several barriers exist to implementing these groups within real-world settings, including community mental health clinics serving children with autism spectrum disorders. Our article identifies these barriers and poses potential solutions to overcoming these obstacles. Specifically, we share adaptations to the implementation of a social skills curriculum in order to meet the needs of an urban, underserved, economically challenged, and diverse population; tailor the curriculum to meet the individual needs of each participant; and facilitate generalization of the learned skills to different settings, most notably the school setting. Effectiveness of these adaptations was measured through assessing parent, teacher, and child perspective of social skills, emotion regulation skills, and anxiety at preintervention, postintervention, and follow-up time points. It is our hope that the adaptations implemented in this setting can be translated to inform social skills groups in other similar settings.